SERVICES AND TAX ADMINISTRATION EASY TO THE COMPLIANCE LEVEL OF MOTOR VEHICLES TAXPAYERS IN PANDEGLANG REGENCY - Emul Mulyana; Surahman Surahman (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
The emergence of the corona outbreak impacted the decline in national taxes; along with this, there was a decrease in the daily receipts of the Banten province motor vehicle tax and an increase in the Banten province vehicle tax arrears. This study aims to analyze the extent to which the quality of tax services and the ease of administrative requirements for paying taxes can affect taxpayer compliance and how much the covid-19 outbreak affects both of these things. The recorded population of two-wheeled vehicles is 216,609 units. The sample processed in this study was 100 respondents obtained by distributing questionnaires with the incidental sampling method in the Samsat area of ​​Pandeglang Regency. Based on the results of data processing, it was found that there was a positive influence of the ease of tax services on taxpayer compliance and no effect on the completeness of tax administration aspects on the level of taxpayer compliance. Therefore, the corona pandemic is not the cause of the low level of compliance of motor vehicle taxpayers. The aspect of the corona pandemic or the covid-19 outbreak is defeated by the ease of tax services provided by the local government. Another thing is that the tax administration has not been able to encourage taxpayer compliance and is estimated to be an obstacle due to several things, such as the difficulty of tax administration during the motor vehicle mutation process. The aspect of the corona pandemic is not the cause of the low level of compliance of motor vehicle taxpayers. Aspects of the corona pandemic or the covid-19 outbreak are defeated by local governments’ ease of tax services. Another thing is that the tax administration has not been able to encourage taxpayer compliance and is estimated to be an obstacle due to several things, such as the difficulty of tax administration during the motor vehicle mutation process. The aspect of the corona pandemic is not the cause of the low level of compliance of motor vehicle taxpayers. The corona pandemic or the covid-19 outbreak is defeated by the ease of tax services provided by the local government. Another thing is that the tax administration has not been able to encourage taxpayer compliance and is estimated to be an obstacle due to